Comparison of isolation of Haemophilus vaginalis (Corynebacterium vaginale) from peptone-starch-dextrose agar and Columbia colistin-nalidoxic acid agar. - Golberg, R L (1976)
A total of 447 cervical or vaginal specimens were inoculated in parallel onto peptone-starch-dextrose (PSD) and Columbia colistin (10 mg/ml)-nalidixic acid (15 mug/ml) (CNA) agar and were incubated for 48 h at 35 degrees C in an atmosphere with 2 to 10% CO2. One hundred (22.4%) of the cultures were positive for Haemophilus vaginalis. Forty-eight of the isolates were recovered from both PSD and Columbia CNA agar, five from PSD only, and 47 from Columbia CNA agar only (P less than 0.001). On Columbia CNA agar, 76 of the isolates were detected after 24 h of incubation, and the remainder were detected within 4 days of incubation.